Organizational Commitment and Identification of Engineers as a Function of Organizational Climate - Barth, R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
This article examines the impact of organizational climate components upon engineers' commitment to, and identification with, their employing organizations. The application of multiple regression analysis indicates that a significant proportion of the variance of the dependent variables can be accounted for by organizational climate scores.